International human resource management in South Korean multinational enterprises - Kang, Haiying; Shen, Jie (Springer Nature Singapore : Palgrave Macmillan, 2017)
In this book, Korean multinational enterprises management strategies in China are analyzed. China is re centering Asia around its newfound economic might, even as neighboring countries such as Japan and Korea will remain more economically developed for generations to come. How do Asian companies adapt to the Chinese market? In this fascinating study, Haiying Kang and Jie Shen investigate how Korean enterprises have adapted human resources practices to the evolving corporate climate in China. Unorthodox blends of culture, legal expectations, and more make the market a truly interesting one to explore HRM practices on the margins. Compelling for academics in HRM but also related social sciences, HR practitioners, and corporate leaders alike, this book is a timely look at new Asian corporate cultures.
The Existing Literature with Respect to International Reward and Compensation of South Korean MNEs.
Keywords: Personnel management -- Korea (South); International business enterprises -- Korea (South); Korea (South); elektronické knihy; electronic books